Turističko i prostorno planiranje u Hrvatskoj i Jugoslaviji 1960-ih Touristic and Spatial Planning in Croatia and Yugoslavia in the 1960s - Kranjčević, Jasenka (2021)
U radu se na temelju tadašnje i recentne (domaće i strane) literature te prostornih planova istražuje međuodnos turističkoga i prostornoga planiranja u Hrvatskoj i Jugoslaviji 1960-ih. Analitičko-interpretativnom metodom proučava se međuodnos tadašnjega društveno-političkog sustava, politika prema turizmu i prostoru, društvenoga planiranja, tijela uprave, institucija specijaliziranih za planiranje, turističkoga prometa, izrađenih prostornih planova, intenziteta izgradnje smještajnih kapaciteta i dr. Zaključuje se da su turističko i prostorno planiranje međusobno bili povezani društvenim planovima razvoja, a rezultati djelovanja u prostoru ovisili su o brojnim, često i nepredvidivim društveno-političkim čimbenicima. U praksi je provedba planova dodatno usložnjena jer su oni često djelovali apstraktno i kontradiktorno u političkom sustavu koji je imao ograničenu sposobnost za provedbu kvalitetnih, ali ponekad i utopijskih ideja.
Based on the contemporaneous and recent (domestic and foreign) literature and spatial plans, this paper examines the relationship between touristic and spatial planning in Croatia and Yugoslavia in the 1960s. The relationship is determined using the analytical-interpretative method of the then socio-political system, tourism and spatial policy, social planning, administrative bodies, institutions specialised for planning, tourist traffic, produced spatial plans, the intensity of building accommodation capacity, etc. In the first period after the end of the war, tourism developed in an uncontrolled manner because it was not the subject of coordinated socio-economic and spatial plans. Due to a growing interest for the inflow of foreign currencies from foreign tourists, tourism gradually gained significance and was regularly given priority in development plans.           The new approach to spatial planning was most visible in the developed methodology of spatial plan production and the hotel architecture and constructed hotel complexes. Since the Croatian coast had the longest Adriatic shoreline in the then Yugoslavia, the longest tradition of tourism, and was the flagship among the republics in tourism development projections and the spatial planning of tourism (because of the developed methodology of plan production), the largest number of touristic spatial plans during the socialist period were made for the Croatian Adriatic coast (on multiple levels), and the greatest investments were made in building hotel capacity there. Despite the initial idea of developing tourism and equal accommodation options for all, the new tourism planning model transformed away from this basic idea and gave priority to exponential economic growth. This new approach to tourism was most visible through the establishment of a new network of organisations and institutions for planning tourism and tourism planning in a broader spatial context rather than only on the level of ind
Bibliografija
Summary.
Keywords: turističko planiranje; prostorno planiranje turizma; povijest prostornoga planiranja i turizma; 1960-e; Hrvatska; Jugoslavija